Carboxylic acid accumulation and secretion contribute to the alkali-stress tolerance of halophyte Leymus chinensis - Wang, Huan; Zhao, Shuting; Sun, Bo; Osman, Feisal Mohamed; Qi, Zexin; Ding, Dan; Liu, Xin; Ding, Jiale; Zhang, Zhian (Frontiers in Plant Science, 2024)
Leymus chinensis is a dominant halophytic grass in alkalized grasslands of Northeast China. To explore the alkali-tolerance mechanism of L. chinensis, we applied a widely targeted metabolomic approach to analyze metabolic responses of its root exudates, root tissues and leaves under alkalistress conditions. L. chinensis extensively secreted organic acids, phenolic acids, free fatty acids and other substances having -COOH or phosphate groups when grown under alkali-stress conditions. The buffering capacity of these secreted substances promoted pH regulation in the rhizosphere during responses to alkali stress. L. chinensis leaves exhibited enhanced accumulations of free fatty acids, lipids, amino acids, organic acids, phenolic acids and alkaloids, which play important roles in maintaining cell membrane stability, regulating osmotic pressure and providing substrates for the alkali-stress responses of roots. The accumulations of numerous flavonoids, saccharides and alcohols were extensively enhanced in the roots of L. chinensis, but rarely enhanced in the leaves, under alkali-stress conditions. Enhanced accumulations of flavonoids, saccharides and alcohols increased the removal of reactive oxygen species and alleviated oxygen damage caused by alkali stress. In this study, we revealed the metabolic response mechanisms of L. chinensis under alkali-stress conditions, emphasizing important roles for the accumulation and secretion of organic acids, amino acids, fatty acids and other substances in alkali tolerance.